Leonurine Regulates Treg/Th17 Balance to Attenuate Rheumatoid Arthritis Through Inhibition of TAZ Expression - Du, Yan-Yi; Chen, Zhi-Xin; Liu, Min-Ying; Liu, Qing-Ping; Lin, Chang-Song; Chu, Cong-Qiu; Xu, Qiang (Frontiers in Immunology, 2020)
Leonurine, an active alkaloid extracted from Herba leonuri, is reported to have potent anti-inflammatory activity against rheumatoid arthritis (RA). However, the molecular mechanism of action of leonurine in RA remains poorly understood. In this study, we detected 3425 mRNAs differentially expressed between CD4+ T cells of RA patients and those of healthy individuals using microarray raw data mining. Kyoto Encyclopedia of Genes and Genomes enrichment analysis revealed that transcriptional coactivator with PDZ-binding motif (TAZ) regulates a variety of biological processes including T-helper (Th)-17 cell development, and was thus selected for functional verification. In a naïve CD4+ T cell differentiation assay, we found that TAZ overexpression was associated with impaired balance between T regulatory (Treg) and Th17 cells in vitro. TAZ overexpression increased the levels of the pro-inflammatory cytokines interleukin (IL)-17, IL-1β, and tumor necrosis factor (TNF)-α and decreased that of the anti-inflammatory cytokine IL-10. Leonurine treatment had a direct recovery effect on the impaired balance and reduced the expression of TAZ and led to normalization of IL-17, IL-1β, and TNF-α and IL-10. Furthermore, IL-6 was found to promote the expression of TAZ and receptor activator of nuclear factor kappa-Β ligand (RANKL), and RANK. Leonurine significantly inhibited TAZ-mediated expression of RANKL, and RANK and IL-6 in synovial fibroblasts. We conclude that the therapeutic effect of leonurine was through suppression of TAZ led to restoration of Treg/Th17 balance and suppression of synovial fibroblast action.